2023
DOI: 10.3390/nano13030434
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanoparticles of Citrate-Coated Manganese Ferrite and Gold Nanorods in Magneto-Optical Imaging and Thermal Therapy

Abstract: The development of nanomaterials has drawn considerable attention in nanomedicine to advance cancer diagnosis and treatment over the last decades. Gold nanorods (GNRs) and magnetic nanoparticles (MNPs) have been known as commonly used nanostructures in biomedical applications due to their attractive optical properties and superparamagnetic (SP) behaviors, respectively. In this study, we proposed a simple combination of plasmonic and SP properties into hybrid NPs of citrate-coated manganese ferrite (Ci-MnFe2O4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Research has found that magnetic hyperthermia is a novel procedure that offers a safe, powerful, and simple treatment method to meet these complicated challenges [92][93][94][95][96]. In this procedure, which has recently seen rapid development, magnetic nanomaterials can be used to improve hyperthermia efficiency compared to traditional hyperthermia methods for the erosion of tumors [97][98][99][100][101][102][103][104][105][106]. The most significant aspect of magnetic hyperthermia is that magnetic nanomaterials are distributed over very small areas so that the temperature behavior of healthy cells is not affected [107][108][109].…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%
“…Research has found that magnetic hyperthermia is a novel procedure that offers a safe, powerful, and simple treatment method to meet these complicated challenges [92][93][94][95][96]. In this procedure, which has recently seen rapid development, magnetic nanomaterials can be used to improve hyperthermia efficiency compared to traditional hyperthermia methods for the erosion of tumors [97][98][99][100][101][102][103][104][105][106]. The most significant aspect of magnetic hyperthermia is that magnetic nanomaterials are distributed over very small areas so that the temperature behavior of healthy cells is not affected [107][108][109].…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%
“…Iron-based nanoparticles also display a combination of interesting magnetic properties with a high biocompatibility that allows the improvement of diagnostic systems such as magnetic resonance imaging (MRI), drug delivery, magnetic separation, cell proliferation and tissue repair, as well as the localized and controlled use of hyperthermia in therapeutics [14][15][16]. They can be iron oxides and ferrites, as well as metal alloy nanoparticles like FePt and FeCo [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of hybrid gold core-shell systems exhibiting more rich physical and chemical properties is known [ 11 , 12 ]. Namely, a combination of gold nanoparticles with materials exhibiting paramagnetic properties is promising for magneto-optical imaging [ 13 , 14 , 15 , 16 ]. Loading the shell with anticancer chemicals or specific oligonucleotide inhibitors is favorable for targeted chemotherapy of cancer with reduced side effects [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%